2017
DOI: 10.1186/s13048-017-0363-y
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis is the independent prognostic factor for survival in Chinese patients with epithelial ovarian carcinoma

Abstract: BackgroundClinico-pathological characteristics and possible prognostic factors among women with epithelial ovarian carcinoma (EOC) with or without concurrent endometriosis were explored.MethodWe retrospectively identified 304 patients with EOC treated primarily at Peking Union Medical College Hospital with median follow-up time of 60 months.ResultsOf 304 patients with EOC, concurrent endometriosis was identified in 69 (22.7%). The patients with concurrent endometriosis were younger and more probably post-menop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recently, an article defined “high-risk” cases as those which share the same mutations present in EOVC and endometriosis, and “low-risk” cases as those not sharing any mutations in endometriosis with the carcinoma ( 30 ). According to the literature, compared with women without endometriosis, women with endometriosis are more likely to be diagnosed with early-stage tumor, with a significantly lower level of serum CA125 before surgery, and are less likely to have lymph node metastasis or to develop platinum resistance disease ( 18 , 31 ). Patients with EOVC arising from endometriosis presented at a lower average age, have a higher percentage of early-stage and lower–grade disease, and are more likely to have no residual disease after primary debulking surgery compared with those without endometriosis, which indicates better survival outcomes ( 32 ).…”
Section: Hypothesis Of Eovc Originmentioning
confidence: 99%
“…Recently, an article defined “high-risk” cases as those which share the same mutations present in EOVC and endometriosis, and “low-risk” cases as those not sharing any mutations in endometriosis with the carcinoma ( 30 ). According to the literature, compared with women without endometriosis, women with endometriosis are more likely to be diagnosed with early-stage tumor, with a significantly lower level of serum CA125 before surgery, and are less likely to have lymph node metastasis or to develop platinum resistance disease ( 18 , 31 ). Patients with EOVC arising from endometriosis presented at a lower average age, have a higher percentage of early-stage and lower–grade disease, and are more likely to have no residual disease after primary debulking surgery compared with those without endometriosis, which indicates better survival outcomes ( 32 ).…”
Section: Hypothesis Of Eovc Originmentioning
confidence: 99%
“…The methodological quality evaluation for the 21 included studies was conducted with reference to NOS, and the results are shown in Table 2 . The NOS scores of the 21 studies ranged from 5 to 8 points, of which 5 points was evaluated for one study ( 23 ), 6 points for five studies ( 21 , 22 , 24 , 33 , 36 ), 7 points for six studies ( 16 , 20 , 25 , 28 , 29 , 31 ) and 8 points for nine studies ( 12 , 15 , 17 , 26 , 27 , 30 , 32 , 34 , 35 ). Overall, the methodological quality of the included studies was moderate.…”
Section: Resultsmentioning
confidence: 99%
“…However, sample sizes were usually small and the results obtained were inconsistent. Some ndings suggest that ovarian endometrial carcinoma and ovarian clear cell carcinoma are early phases with better prognosis than the two pathological types of primary ovarian cancer [20][21], while other researchers have reported no obvious differences [22][23]. Here, we examined 174 cases of ovarian endometrial carcinoma and clear cell carcinoma, with a median follow-up period of 67 months.…”
Section: Discussionmentioning
confidence: 99%